Heat transfer enhancement through different heat sink/impinging air jet parameters an experimental approach - Beriache, M'hamed; Cherki, Brahim Hicham; Mokhtar Saïdia, Leila; Nor Azwadi, Che Sidik; Rizalman, Mamat (Kauno Technologijos Universitetas, 2023)
In the present work, improving the thermal performance of a central processing unit (CPU) cooling system consisting of a plate fin minichannel heat sink exposed to an air jet of impact is accomplished. The height of the impinging air jet duct, the mode of air flow on the heat sink, air blowing mode and as well as the suction blow mode "pull" and the air jet duct geometry are three important influence parameters on the phenomenon. The results obtained show that a jet height H = 20 mm, a convergent duct of H = 40 mm in height and a hair dryer tip provide further improvement of the cooling technique. The two preceding parameters combined with the fan air suction blow mode improve the performance by at least 11,2% compared to the initial configuration (marketed product), having as characteristics (H= = 0 mm, fan in the blowing push mode). The use of a converging duct and a hair dryer conduit show that the velocities from the hair dryer tip far exceed those from the best standard conduit height, H = = 20 mm. That said, the improvement of the flow in the central zone is substantially achieved, which consequently improves the heat removal in this zone at least 19%.